2021
DOI: 10.4102/sajid.v36i1.209
|View full text |Cite
|
Sign up to set email alerts
|

Lack of resistance to macrolides in Mycoplasma genitalium detected in South African pregnant women

Abstract: Background: Azithromycin regimens have been considered first-line treatment for Mycoplasma genitalium (M. genitalium), a sexually transmitted infection (STI) associated with adverse pregnancy outcomes. However, recent years have seen rapid emergence of macrolide resistance in M. genitalium as a result of widespread administration of azithromycin. Currently, there are limited data on macrolide resistance in pregnant women from KwaZulu-Natal (KZN), South Africa. This study investigated the prevalence of M. genit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…22 A recent study conducted among pregnant women in KwaZulu-Natal, South Africa reported a prevalence of 5.9% for M. genitalium . 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A recent study conducted among pregnant women in KwaZulu-Natal, South Africa reported a prevalence of 5.9% for M. genitalium . 23…”
Section: Discussionmentioning
confidence: 99%
“…22 A recent study conducted among pregnant women in KwaZulu-Natal, South Africa reported a prevalence of 5.9% for M. genitalium. 23 Numerous demographic and behavioral factors have been reported to be associated with M. genitalium infection. 8,13 In women, young age, with a low education level, originating from sub-Saharan Africa, having ≥6 sexual partners in the last 6 months, onset of sexual activity after 20 years of age, HIV positivity, and co-infection with other STIs have been associated with a higher risk of having M. genitalium infection.…”
Section: Discussionmentioning
confidence: 99%